Gambaran Pengetahuan dan Sikap Remaja Kelas VIII Tentang Lesbian, Gay, Biseksual, Transgender (LGBT) di SMP Negeri 24 Padang - Riska Pitriyani; IIs Niawati (Nursing Applied Journal, 2025)
According to the Indonesian Ministry of Health's report on HIV cases for the period January – March 2017, the total number of HIV virus infections reported was 10,376 people. The highest percentage of HIV factors in risky sex was among men who have sex with men (MSM) (28%), heterosexuals (24%), injecting needles (2%) and others (9%). In the West Sumatra region, in 2022, in 4 points, namely Padang City, Bukitinggi, Solok and Solok Regency, it is estimated that there will be 14,469 people who have sex with men (MSM) or gay people in West Sumatra (Ministry of Health of the Republic of Indonesia, 2022). The aim of this research is to determine the description of the knowledge and attitudes of class VIII teenagers regarding LGBT at SMP Negeri 24 Padang in 2024.This type of research is "analytical" with a cross sectional design. This research was conducted in May-September 2024 at SMP Negeri 24 Padang. The population of this study were all students in class VIII of SMP Negeri 24 Padang. The sampling technique with a sample size of 73 people was simple random sampling. Data collection uses primary and secondary data. Univariate analysis uses descriptive statisticsThe research results show that from the results of data processing from SPSS, 28.8% of teenagers have good knowledge and 71.2% have sufficient knowledge. And for the assessment of adolescent attitudes, 46.6 were positive and 53.4 were negative. With a sample of 73 respondents.It was concluded that 71.2% of teenagers had sufficient knowledge about Lesbian, Gay, Bisexual, Transgender (LGBT). From the attitude of teenagers who behave negatively, 53.4% ​​are also expected for schools to be able to further increase the provision of knowledge about (LGBT), especially the impacts or dangers of (LGBT). This can further increase teenagers' knowledge, especially about the dangers of (LGBT).